The perspectives of visual arts teachers on postmodernism - İsmail Tetikci; Gonca Erim; Kevser Baykan (International Journal of Evaluation and Research in Education (IJERE), 2024)
Postmodernism has evolved in the field of art, and its presence and definition have been the topic of several studies. The overall perspectives of the visual arts teachers on postmodernism are important for incorporating postmodernism issues into the high school curriculum in Turkey, as they are teaching art history and conveying the practice of visual arts. A review of the literature reveals that there are no comparable studies that take visual arts teachers’ perspectives on postmodernism into account. Therefore, this study aims to discover the perspectives of visual arts teachers on postmodernism. This article presents the findings and conclusions of the first research question of the Master’s thesis, titled “examination of the reflections of postmodernism on art education”. The study used a case study design, one of the qualitative research approaches. The sample of the study consisted of four visual arts teachers working in one of the central and three district schools in Yalova, Turkey. In the current research, two semi-structured interview forms and document analysis were utilized as data collection tools. The qualitative data were analyzed by the thematic analysis method. The themes of “teachers’ general perceptions”, “teaching process” and “reflection on students” were identified through the thematic analysis. This article includes a detailed analysis of the theme of “teachers’ general perceptions”. The results of the research identified the artistic and intellectual perspectives of the participating teachers toward postmodernism as outstanding features.